Hubungan Antara Manajemen Risiko Kredit dan Faktor Spesifik Bank terhadap Kinerja Keuangan pada Bank di ASEAN-5 - Parasdya, Yoga; Raharja, Surya (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study aims to identify and analyse the effects of credit risk management and bank-specific factors on bank financial performance. Credit risk management is explained by non-performing loan ratio (NPL) and capital adequacy ratio (CAR), while bank specific factors are explained by cost to income ratio (CIR), net interest margin (NIM) and loan to deposit ratio (LDR). Financial performance is explained by return on assets (ROA). The object of this research is banks listed on the stock exchange in Indonesia, Malaysia, Singapore, Thailand and Philippines or ASEAN-5. The sample of this study is 63 banks with an observation period during 2017-2022 which resulted in 378 data. The results of this study are NPL and CAR have a negative and significant effect on ROA. This means that weak credit risk management can affect the decline in ROA. CIR and LDR have a negative and significant effect on ROA, meanwhile NIM has a positive and significant effect. This means that weak intermediation activities between depositors and creditors can also affect the decline in ROA. This study is different from previous studies because it adds the age of the bank as a control variable and expands the observation subjects to ASEAN-5 countries and extends the observation period.